Chronic venous insufficiency – an update. Part II – prophylaxis, conservative therapy - Żmudzińska, Maria (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
This paper is the second one in the series of articles concerning chronic venous insufficiency (CVI). We present the review of data on prophylaxis and conservative therapy. General purpose of various therapeutic methods is reduction or elimination of venous hypertension. Life style, physiotherapy, compression therapy and pharmacotherapy are crucial elements of both prophylaxis and conservative therapy. Physical activity should be composed with the adequate relax including correct legs elevation. Compression therapy includes the use of compression bandages and stockings. Pressure induced by compression bandages or stockings involves not only veins, but also arteries, lymphatic vessels, tissues and fibrinolisis system. Pharmacotherapy is also the crucial part of both prophylaxis and conservative therapy. Proper, based on the knowledge of CVI pathomechanism prophylaxis and administration of conservative therapy methods may improve the clinical status of patients and delay the disease progress. chronic venous insufficiency, prophylaxis, conservative therapy.